1998
DOI: 10.1007/s001250050976
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immune responses to β casein: elevated in but not specific for individuals with Type I diabetes mellitus

Abstract: Type I diabetes mellitus appears as the end result of an autoimmune destruction of the insulin secreting pancreatic beta cells [1]. The immunological mechanisms underlying the development of Type I diabetes mellitus as well as the role of environmental agents (e. g. diet, viruses, stress) in the pathogenesis of the disease have been the subject of considerable research. The rationale for investigating environmental agents involves an attempt to explain numerous epidemiological observations including the diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
1

Year Published

1999
1999
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 9 publications
4
17
0
1
Order By: Relevance
“…We previously reported enhanced cellular immune response to bovine -casein in patients with type 1 diabetes (Cavallo et al 1996b) and this was confirmed by other authors (Ellis et al 1998). However, a similar increase was noticed also in first degree relatives of type 1 diabetes probands (Ellis et al 1998), pointing out the role of genetic susceptibility in this response.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…We previously reported enhanced cellular immune response to bovine -casein in patients with type 1 diabetes (Cavallo et al 1996b) and this was confirmed by other authors (Ellis et al 1998). However, a similar increase was noticed also in first degree relatives of type 1 diabetes probands (Ellis et al 1998), pointing out the role of genetic susceptibility in this response.…”
Section: Introductionsupporting
confidence: 78%
“…However, a similar increase was noticed also in first degree relatives of type 1 diabetes probands (Ellis et al 1998), pointing out the role of genetic susceptibility in this response.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Nonetheless, the majority of studies published to date have not reported differences in response rates to antigens unrelated to -cells between diabetic and control subjects, which is consistent with the results of most participants in the workshop. It may be important to extend the number of control stimuli tested in order to assess specificity of the proliferative response, for instance by inclusion of cocktails of vaccine antigens (PPD, tetanus toxoid, candida albicans) [66]. This may provide a standard reference value as positive control, which is more constant than the results obtained with individual antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Increased T cell immunity to beta casein has been reported in patients with newly diagnosed type 1 diabetes [Cavallo et al, 1996] but also in their unaffected relatives [Ellis et al, 1998]. This indicates that a genetic failure in the regulation of the immune response to this dietary protein may be related to type 1 diabetes.…”
Section: Cow's Milk Proteinsmentioning
confidence: 99%